Hypoxia Alleviating PdTe Nanoenzymes for Thermoradiotherapy - Li, Yang; Gu, Xinquan; Yu, Fan (Frontiers in Bioengineering and Biotechnology, 2022)
Hypoxia in the tumor microenvironment induces radioresistance in cancer cells, which reduces the treatment efficiency of radiotherapy. Therefore, it is critical to produce sufficient oxygen to alleviate hypoxia to enhance the effect of ionizing radiation. Here, we constructed nanorod-shaped PdTe nanoenzymes to overcome hypoxia and promote the effects of thermoradiotherapy. Both palladium and tellurium are high-Z elements, which interacted with X-rays to generate more DNA radicals in the tumor regions. Moreover, PdTe nanoenzyme could catalyze the conversion of intratumoral overexpressed H2O2 to oxygen, alleviating hypoxia in the tumor regions. Photothermal therapy mediated by PdTe nanoenzymes not only ablated tumors but also accelerated the blood flow, in turn, modulating hypoxia. With good biocompatibility, PdTe nanoenzyme exhibited remarkable oxygen generation ability both in vitro and in vivo, indicating potential ability for radiosensitization. Further investigation using MBT-2 cells and MBT-2 tumor-bearing mice demonstrated that PdTe nanoenzyme could effectively enhance the treatment efficiency of radiotherapy. Thus, our work presented a novel nanoenzyme to overcome hypoxia in tumors for effective thermoradiotherapy.